'I acted like a man': exploring female ex-insurgents' narratives on Nigeria's oil insurgency. Issue 149 (2nd July 2016) - Oriola, Temitope
Abstract : This paper explores how a small sample of female ex-insurgents make sense of their engagement in Nigeria's oil insurgency. The study is informed by three key questions: How did Delta women join the insurgency? Why did they join? How do they frame their participation? The paper analyses the prevalence of a masculinising rhetoric among participants. The majority of participants view their roles in the insurgency as antithetical to their gender. The implications of these findings are explored. Overall, the paper contributes to the growing body of work on women's engagement in armed conflict as perpetrators rather than victims of violence.